The interaction between grain boundary and tool geometry in nanocutting of a bi-crystal copper. (28th October 2019) - Wang, Zhanfeng; Sun, Tao; Zhang, Haijun; Li, Guo; Li, Zengqiang; Zhang, Junjie; Yan, Yongda; Hartmaier, Alexander
Abstract: Anisotropy is one central influencing factor on achievable ultimate machined surface integrity of metallic materials. Specifically, grain boundary has a strong impact on the deformation behaviour of polycrystalline materials and correlated material removal at the microscale. In the present work, we perform molecular dynamics simulations and experiments to elucidate the underlying grain boundary-associated mechanisms and their correlations with machining results of a bi-crystal Cu under nanocutting using a Berkovich tool. Specifically, crystallographic orientations of simulated bi-crystal Cu with a misorientation angle of 44.1° are derived from electron backscatter diffraction characterization of utilized polycrystalline copper specimen. Simulation results reveal that blocking of dislocation motion at grain boundaries, absorption of dislocations by grain boundaries and dislocation nucleation from grain boundaries are operating deformation modes in nanocutting of the bi-crystal Cu. Furthermore, heterogeneous grain boundary-associated mechanisms in neighbouring grains lead to strong anisotropic machining behaviour in the vicinity of the grain boundary. Simulated machined surface morphology and machining force evolution in the vicinity of grain boundary qualitatively agree well with experimental results. It is also found that the geometry of Berkovich tool has a strong impact on grain boundary-associated mechanisms and resultant ploughing-induced surface pile-up phenomenon.